Synthesis, characterization and catalytic performance of Cu/ZnO/SBA-15 for hydrogen of carbon dioxide to methanol - Nurul Ain, Mohamed Razali (2014)
Carbon dioxide (CO2) is the primary greenhouse gas that causes global warming. The conversion of CO 2 into methanol (CH3 0H) is an alternative to the costly geological and oceanic CO 2 sequestration. CH30H is an important feedstock in the chemical industries and known as an alternative fuel. The catalytic CO2 conversion and CH30H space time yield (STY) is however reported to be considerably low. It is therefore of importance to develop novel catalysts with improved properties for catalytic growth. Santa Barbara Amorphous 15 (SBA-1 5) with highly ordered hexagonal structure, uniform pore diameter ('-'5.5 nm) and particle morphology, thicker wall-thickness (3.0 to 5.0 nm), high surface area (585.20 M2 /g) and high thermal stability was successfully synthesized by the conventional method without hydrothermal aging process. The synthesized SBA-15 was used as catalyst support. A number of monometallic and bimetallic catalyst of copper (Cu) or/and zinc oxide (ZnO) supported on SBA-15 were synthesized by simple reflux method. The physicochemical properties of the as-prepared catalysts were investigated by X-ray diffraction (XRD), nitrogen adsorption, thermogravimetric analysis (TGA), scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDX), transmission electron microscopy (TEM), and hydrogen-temperature programmed reduction (H 2-TPR). The best amount of 5 wt.% Cu and 15 wt.% ZnO supported on SBA-1 5 designated as SCull 5ZnO/SBA-1 5 was found to effectively catalyze the hydrogenation of CO 2 to CH3 011. The best process conditions for CO2 hydrogenation to CH30H over 5Cu/15ZnO/SBA-15 were found to be the reaction pressure of 4.0 MPa, the reaction temperature of 250 °C, and the reactants total gas hour space velocity (GHSV) of 2400 h' that resulted to 22.9% and 11796.8 mmol kgcat' h' of CO2 conversion and CH30H STY, respectively. A reaction mechanism of CH 30H synthesis route and reverse water gas shift (RWGS) reaction on CulZnO/SBA-15 was proposed, based on the experimental results obtained in this study. The calculated activation energies of CH 30H synthesis and carbon monoxide (CO) formation were 35.29 kJ/mol and 68.02 kJ/mol, respectively. The CO2 conversion and CH30H STY were stable during 24 h of reaction on stream and no obvious deactivation was observed. The higher catalytic activity obtained over the novel SCu/l 5ZnO/SBA-15 catalyst can be correlated to the high dispersion of Cu and ZnO on the SBA-15 surfaces, creating greater amount of Cu-ZnO active sites, which are necessary for CH30H synthesis route. The deposited ZnO migrationon the Cu surfaces was found to deactivate the RWGS reaction to form CO; and therefore increasing the CH30H selectivity.